A132 THREE QUARTERS OF INFLAMMATORY BOWEL DISEASE PATIENTS ON MAINTENANCE INFLIXIMAB THERAPY IN CLINICAL REMISSION SHOW EVIDENCE OF MUCOSAL INFLAMMATION WITH ELEVATED FECAL CALPROTECTIN. (1st March 2018) - Stern, N; Wong, K; Dieleman, L A; Halloran, B P; Huang, V; Kroeker, K I; Peerani, F; van Zanten, S; Fedorak, R
Abstract: Background: Fecal calprotectin (FCP) has been demonstrated to be a noninvasive marker of mucosal inflammation and when elevated, correlates with endoscopic mucosal disease activity in patients with Ulcerative Colitis (UC) and Crohn's Disease (CD). Endoscopic mucosal healing and normalization of FCP represents desired therapeutic results in these patients as it has shown to improve patient outcomes by reducing hospitalization and surgery. Aims: To determine the proportion of patients with UC and CD in clinical remission on maintenance infliximab (IFX) therapy who had elevated FCP test results. Methods: Sequential UC and CD patients over 18 years of age attending an IFX infusion clinic at the University of Alberta completed a Partial Mayo Score (pMS) or Harvey Bradshaw Index (HBI), as a determinant of clinical remission or disease activity, and were given a FCP test kit to voluntarily complete and return. FCP was determined using ELISA methodology. Results: FCP test kits were given to 243 patients and 98 (40.3%) returned the kit for analysis (22 UC, 76 CD). Patients were separated by 4 categories: FCP ≥ 250 mcg/g, FCP ≥ 100 mcg/g, FCP < 250 mcg/g and FCP < 100 mcg/g. Twenty-three patients had FCP levels ≥ 250 (8 UC, 15 CD) of which, 78.3% were in remission, as indicated by pMS or HBI. Forty-one patients had FCP levels ≥ 100 (12 UC, 29 CD) of which, 73.2% were in clinical remission. Seventy-four patients had FCP levels < 250 (14 UC, 60 CD), of which, 79.7% were in clinical remission. Fifty-six patients had FCP levels < 100 (10 UC, 46 CD) of which, 83.9% were in clinical remission. Table 1 summarizes patient results for UC and CD. Conclusions: Over 75% of patients on maintenance IFX therapy identified as being in clinical remission, as per disease activity scoring, yet show evidence of mucosal inflammation with elevated FCP tests. This suggests that to achieve a therapeutic outcome of mucosal healing with inflammatory bowel disease therapy, objective monitoring should be routinely conducted in all patients. Funding Agencies: None